The urban process of an arcade street in late Ottoman Istanbul: demolitions, renovations and relocations in Direklerarası (1880-1911) - Tunc Yasar, Fatma (CAMBRIDGE UNIV PRESS, 2025)
Direkleraras & imath; Street was a popular promenade and entertainment hub in late Ottoman Istanbul. It was constructed in the arasta form along the historical Divanyolu in the 1720s and largely retained its spatial configuration until the 1880s. This article examines the spatial transformation of Direkleraras & imath; Street from the 1880s to the 1910s, situating it within the broader dynamics of late Ottoman urban reform. It investigates urban interventions such as the demolition and reconstruction of arcade columns, street lighting, pavement reconfigurations and square design, not merely as outcomes of modern urban regulations but also as processes intricately linked to the various dynamics shaped by the sociopolitical and cultural contexts of the late Ottoman capital.
Keywords: SPACE; History